Digital archiving of traditional songket motifs using image processing tool - Jamil, Nursuriati; Tengku Sembok, Tengku Mohd; Abu Bakar, Zainab (WSEAS, 2012)
This paper presents an image processing tool, part of an image retrieval system, that provides digitization of songket motifs extracted from songket patterns. Songket motifs are acquired from their original songket fabrics and digitized into binary form by using several image processing techniques. This paper describes the digitization process and experiments conducted on fifty textile motifs using image processing techniques: contrast enhancement, noise reduction, binarization and morphological operations.